Peran Granulasi dan Pengayaan Terhadap Peningkatan Efektivitas Kompos pada Sawi, Selada, Kangkung, dan Bayam - Yudi Sastro, I krarwati, Suwandi (Jurnal Hortikultura Indonesia, 2012)
ABSTRACTThis  study  aimed  at  determining  the  effect  of  granulation  and  compost  enrichment  to  improve  the effectivity of compost on green mustard, lettuce, kangkong, and spinach. The granulation treatments i.e without and  with  granulation  and  the  enrichment  using  microbial  cultures,  the  liquids  from  the  rock  phosphate fermentation, and the mixture of microbial cultures and the liquids from the rock phosphate fermentation were as treatments . The combinations  of treatments  were  arranged using completely  randomized  block  design with 20 replications. Variables observed were plant height, leaf number, fresh weight and dry weight. The data were analyzed using analysis of variance  and foll owed by Duncan's Multiple Range Test.  The results showed that there was no significant interaction between granulation with enrichment to improve the effectivity of compost on green mustard, lettuce, kangkong, spinach. The compost granulation treatment significantly increased the effectivity of compost on green mustard and lettuce, but not  on  kangkong and spinach. The granulation even decreased  the compost effectiveness on spinach. The compost enrichments treatments significantly increased the effectivity of compost on green mustard, lettuce and spinach. The compost enrichments using the mixture of liquid fermentation medium of rock phosphate and microbial increased yield of green mustard and lettuce up to 48.4 and 60.1% respectively, while liquid fermentation medium of rock phosphate increased yield of spinach 75.0%.Key words: compost, granulation, enrichment, vegetableABSTRAKPenelitian  ini  bertujuan  untuk  mengetahui  pengaruh  granulasi  dan  pengayaan  terhadap efektivitas kompos pada sawi, selada, kangkung, dan bayam. Perlakuan penelitian terdiri atas perlakuan granulasi,  yakni  tanpa  dan  dengan  granulasi,  dan  perlakuan  pengayaan  yang  meliputi  kultur  mikroba, cairan media fermentasi batuan fosfat, dan campuran kultur mikroba dan cairan media fermentasi batuan fosfat.   Kombinasi  perlakuan  diatur  menggunakan  Rancangan  Acak  Kelompok  Lengkap  dengan pengulangan  sebanyak  20  kali.  Peubah  pengamatan  meliputi   tinggi  tanaman,  jumlah  daun,  dan  berat segar  serta  berat  kering  tanaman.   Data  hasil  pengamatan  dianalisis  menggunakan  analisis  varian  dan dilanjutkan  menggunakan   Duncan  Multiple  Range  Test.  Hasil  penelitian  menunjukkan  bahwa  tidak terdapat  interaksi  nyata  antara  perlakuan  granulasi  dan  pengayaan  terhadap  peningkatan  efektivitas kompos  pada  sawi,  selada,  kangkung  dan  bayam.  Perlakuan  granulasi  nyata  meningkatkan  efektivitas kompos  pada  sawi  dan  selada,  namun  tidak  pada  kangkung  dan  bayam.   Perlakuan  granulasi  bahkan menurunkan efektivitas kompos pada bayam.  Pengayaan  nyata  meningkatkan efektivitas kompos pada sawi, selada, dan bayam. Pengayaan  kompos menggunakan campuran kultur mikroba dan cairan medium fermentasi  batuan  fosfat  meningkatkan  hasil  sawi  dan  selada,  masing-masing  hingga  48,4  dan  60,1%, sedangkan cairan medium fermentasi batuan fosfat meningkatkan hasil bayam sebesar 75%.Kata kunci: kompos, granulasi, pengayaan, sayuran